Conservation of Water Resources Around Rivers as an Effort to Empower the Community in Kalong Liud Village - Effendi, Herlinda; Amelia, Nisa; Gymnasti, Alista Dwis; Sutanto; Mulyati, Ade Heri; Warnasih, Siti (Jurnal Pengabdian Masyarakat Inovatif, 2024)
Program Penguatan Kapasitas Kemahasiswaan team (PPK Ormawa) of Himpunan Mahasiswa Kimia (HIMASKA) of the Faculty of Mathematics and Science, Pakuan University has implemented a water resource conservation program to overcome floods and droughts that occur every year in Kalong Liud Village, Nanggung District, Bogor Regency, West Java Province. Water resource conservation with green ampel bamboo (Bambusa vulgaris Schrad. ex. J.C) uses a combination of vegetative and agronomic methods with the aim of maximizing erosion control and surface flow of the Cikaniki River. This program began with a survey of village locations, socialization and education to maximize the sustainability of the implementation of the program by holding pre-tests and post-tests for community groups and residents around the Cikaniki River. After that, green ampel bamboo was planted on the cleared and dug land 50 cm deep with a hole diameter of 15 cm. The growth of green ampel bamboo is monitored and evaluated once a week to find out how to optimize its growth. As a result, young leaves grow from bamboo books after 3 (three) weeks of planting and maintenance. In addition, the provision of education and scientific approaches can increase public understanding and awareness of climate change that can cause flood disasters.